A mulher-mãe em (dis)curso: a cena enunciativa na rede social Instagram - Silva, Alice Rios Carini (2024)
The way in which society is transformed through the different technological resources at its disposal inspires the construction of this master's research, by asking questions about women in the role of mother in digital media. The objectives we set are: to weave reflections on how the discursive construction of what it means to "be a mother" on Instagram takes place, to check whether there is a movement of (re)signification of this woman's performance when circulated on the Web, to identify the main regularities and irregularities around statements that contain definitions of “mother” both in traditional dictionaries and in posts on the social network Instagram. And, thus, we answer the following question: can the woman-mother, when symbolically portrayed and defined on the social network Instagram, be linked to a scenography of idealization and romanticization of motherhood? To this end, we will base ourselves theoretically and methodologically on the analysis of French discourse with an enunciative basis undertaken by Dominique Maingueneau (2008, 2015) in his studies regarding scenes of enunciation and we will also use as theoretical material ideas from Marie-Anne Paveau (2021) about the analysis of Web 2.0 digital discourse. Considering the functioning of digital discourse, interpreting testimony by testimony, to analyze the scenes of the statement, analyzing the encompassing scene, the generic scene and the scenography of the speeches behind each definition of the woman-mother, for this we will consider language as a matter of discursive event, producing a certain utterance. The corpus of analysis is found in profiles on the social network Instagram that try, in an ironic way, to present the meaning of what it means to “be a mother” and describe motherhood. By reading these materials, we are checking whether there is a movement of (re)signification of this role of women when circulated on the Web. The idea is not to make comparisons between posts, but rather to find a pattern of reproduction in the definitions, to understand how the digital medium defines “being a mother”. Our hypothesis is that these discourses that circulate in certain profiles solidify the image of women as multitaskers, who dedicate themselves to their family out of love and should be the sole caregiver for their children.